Early village dwellings and the reproduction of South Andean formative communities - Salazar, Julián (2015)
Fil: Salazar, Julián. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Centro de Investigaciones María Saleme de Burnichón; Argentina.